Faktor – Faktor Yang Mempengaruhi Nilai Perusahaan Melalui Corporate Social Responsibility (CSR) - Mardi, Mardi; Hermanto, Hermanto; Widyastuti, Erna (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p25, 2019)
The company's short-term goals to maximize profits and long-term goals to increase company value. The purpose of this study is to determine the effect of company size, board of commissioners, bonus planning, and financial performance on firm value through CSR disclosure. The study population was 172 companies with a total sample of 113 companies. The data analysis technique uses path analysis. Statistical results show that firm size does not affect CSR disclosure or company value, bonus planning does not affect CSR disclosure but affects company value, while board of commissioners and financial performance influence CSR disclosure and company value, while CSR disclosure has an effect on firm value but not yet able to become an intervening variable. Keywords : F irm sizes; board of commissioners; bonus planning; financial performance; CSR; firm value